L-MOCA: An open-label study of olaparib maintenance monotherapy in platinum-sensitive relapsed ovarian cancer - Gao, Qing-lei; Zhu, Jianqing; Zhao, Weidong; Huang, Yi; An, Ruifang; Zheng, Hong; Qu, Pengpeng; Wang, Li; Zhou, Qi; Wang, Danbo; Lou, Ge; Wang, Jing; et al. (Journal of clinical oncology, 2021)
e17526Background: In patients with platinum-sensitive recurrent serous ovarian cancer, maintenance monotherapy with the poly (ADP-ribose) polymerase inhibitor (PARPi) olaparib, significantly improves progression-free survival (PFS) versus placebo. This is the first study to evaluate the efficacy and tolerability of the olaparib (Lynparza), an oral PARPi, in patients with platinum-sensitive relapsed (PSR) ovarian cancer, carried out exclusively in Asia. Methods: In this open-label, single arm trial, patients with PSR high grade epithelial ovarian cancer who had received ≥2 previous lines of platinum-based chemotherapy with a response, were enrolled from 28 centres in China and Malaysia. All patients received oral olaparib (300 mg) tablet twice daily until disease progression or unacceptable toxicity. The primary endpoint was PFS assessed by investigator according to RECIST 1.1 criteria. Secondary endpoints included time to TFST, PFS2, TSST, OS, and safety endpoints included adverse events (AEs). Subgroup analysis of PFS was examined by BRCA status. Data were summarized by descriptive statistics; time-to-event endpoints were analyzed using Kaplan-Meier method. Primary analysis was performed when 60% of PFS events had been achieved. Results: Between 2018 and 2020, the 224 patients recruited into this study received oral olaparib (full analysis set). 224 patients (91.5% from China and 8.5% from Malaysia) provided BRCA mutation status by blood and tissue testing. 47.3% patients were BRCAm, 41.1% patients were gBRCAm,52.2% patients were BRCAwt and 0.4% patients were BRCA unknown. 35.7% patients had received ＞2 lines of chemotherapy. At data cut-off (Dec 25th, 2020), 139 patients had disease progression; median PFS (mPFS) was 16.1 (95% CI 13.3-18.3) m in all patients. The mPFS was 21.2m, 21.4m and 11.0m in BRCAm, gBRCA and BRCAwt subgroups, respectively. The overall incidence of any AE and SAE was 99.1% and 25.4%, respectively. There were 9.4% patients who discontinued therapy due to the treatment related AE. The most common AEs were anemia, nausea and vomiting. Conclusions: The L-MOCA study demonstrates olaparib maintenance treatment is effective and well tolerated in Asian PSR ovarian cancer patients regardless of BRCA status. Clinical trial information: NCT03534453.Overall population (N = 224)sBRCAm (N = 106)gBRCAm (N = 92)BRCAwt (N = 117)Clinical outcomes With events, n (%)139 (62.1)56 (52.8)*48 (52.2)*82 (70.1)* mPFS, months (95% CI)16.1 (13.3-18.3)21.2 (16.4-24.9)21.4 (16.5-24.9)11.0 (8.3-15.8)Safety, n (%) Any AE220 (98.2) TRAE leading to treatment   discontinuation21 (9.4)MDS/AML3 (1.3)Percentages are based on the number of subjects in analysis population. *Calculated based on the number of patients in each subgroup. mPFS, median progression-free survival; TRAE, treatment-related AE; MDS, myelodysplastic syndrome; AML, acute myeloid leukemia.